Gamma-glutamyltransferase level in pregnancy is an independent risk factor for gestational diabetes mellitus - Tan, P.C.; Mubarak, S.; Omar, S.Z. (2008)
Aim: To evaluate the relationship between gamma-glutamyltransferase (GGT) level in pregnant women at oral glucose tolerance test (OGTT) and the diagnosis of gestational diabetes (GDM). Methods: Blood was taken for analyzing GGT level from women at high risk of GDM at the time of their scheduled OGTT. GDM was diagnosed according to World Health Organization 1999 criteria. Results: GGT level correlated positively with the 2-hour glucose level (Spearman's rho = 0.112: P < 0.05). GGT values that were stratified into quartiles demonstrated a significant trend with diagnosis of GDM (chi(2) for trend; P = 0.03). Multivariable logistic regression analysis taking into account maternal age, gestational age at OGTT, body mass index and a positive 50-g glucose challenge test (GCT) indicated that high GGT was an independent risk factor for GDM (adjusted odds ratio AOR 2.1 95% CI 1.2-3.8: P = 0.01). In the subset of women identified by a positive GCT, on multivariable logistic regression analysis, only high GGT was an independent risk factor for GDM (AOR 2.3 95% CI 1.3-4.2: P = 0.007). Conclusion: Raised GGT level is an independent risk factor for GDM in high risk pregnant women undergoing OGTT.